Impacts of Short-Term Grazing Intensity on the Plant Diversity and Ecosystem Function of Alpine Steppe on the Qinghai–Tibetan Plateau - Xinghai Hao; Juejie Yang; Shikui Dong; Hao Shen; Fengcai He; Yangliu Zhi; Emmanuella A. Kwaku; Danjia Tu; Shengyun Dou; Xueli Zhou; Zhengrong Yang (Plants, 2022)
Livestock grazing is the primary land use of grasslands worldwide. Grazing has been asserted to alter grassland ecosystem functions, such as productivity, nutrient cycling, and biodiversity conservation. However, few studies have focused on the impact of grazing intensity on the ecosystem multifunctionality (EMF) of alpine grasslands. We conducted a field experiment of manipulating sheep grazing intensity effects on alpine steppe by surveying plant community characteristics and ecosystem functions. Our results showed that plant community composition was altered with increasing grazing intensity, and the dominant species shifted from grasses and sedges to forbs. EMF was the highest under no grazing (CK) and the lowest under heavy grazing (HG), but there was insignificant difference between CK and HG. HG significantly decreased some indicators that reflected nutrient cycling functions, such as soil available nitrogen, plant leaf nitrogen (PN) and phosphorus content (PP). Furthermore, plant diversity had strong correlations with SOC, total nitrogen (TN), and PN. The results could provide scientific bases for biodiversity conservation and sustainable grazing management of alpine steppe.